1967
DOI: 10.1128/aem.15.1.31-34.1967
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Activity in the Presence of Agar

Abstract: Agar has been shown to interfere with the activity of some antibiotics against Staphylococcus aureus. This interference has been observed as an increase in the minimal inhibitory concentration and in the diameter of the zone of inhibition. Purifying the agar with water extractions substantially reduced this adverse effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1970
1970
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Sands and Bennett (33) have demonstrated that some phenolic compounds are less inhibitory to Staphylococcus aureus in unwashed agar, and that inhibition can be restored by washing agar cubes in distilled water before adding the agar to growth media. Similar agar effects have been shown for fatty amines (23), antibiotics (15,24,38), and infectivity of Dengue virus (34). Greenberg (19) has studied removal of agar factors with water, methyl alcohol, ethyl alcohol, acetone, and butanoi.…”
Section: Agar Plug Diffusion Culturesmentioning
confidence: 55%
“…Sands and Bennett (33) have demonstrated that some phenolic compounds are less inhibitory to Staphylococcus aureus in unwashed agar, and that inhibition can be restored by washing agar cubes in distilled water before adding the agar to growth media. Similar agar effects have been shown for fatty amines (23), antibiotics (15,24,38), and infectivity of Dengue virus (34). Greenberg (19) has studied removal of agar factors with water, methyl alcohol, ethyl alcohol, acetone, and butanoi.…”
Section: Agar Plug Diffusion Culturesmentioning
confidence: 55%
“…A few studies have examined the influence of agar on antimicrobial activity (9,13). For example, antibiotics such as aminoglycosides and polymyxins are bound to negatively charged groups on the agar molecule (6).…”
Section: Discussionmentioning
confidence: 99%
“…Agarose probabiy affects germination by interfering with the cation supply of P. hyoscyami. Hanus et al (1967) noted that divalent cations, including calcium and magnesium, were often bound to agar. The purification process used to prepare agarose from agar involves chemically removing all impurities and undesirable components (Duckworth & Yaphe, 1971).…”
Section: Discussionmentioning
confidence: 99%